Molecular phylogenetic analyses reveal multiple long-distance dispersal events and extensive cryptic speciation in Nervilia (Orchidaceae), an isolated basal Epidendroid genus - Gale, Stephan W.; Li, Jihong; Suddee, Somran; Traiperm, Paweena; Peter, Craig I.; Buruwate, Tomas; Crain, Benjamin J.; McCormick, Melissa K.; Whigham, Dennis F.; Musthofa, Arni; Gogoi, Khyanjeet; Ito, Katsura; et al. (Frontiers in Plant Science, 2025)
The terrestrial orchid genus Nervilia is diagnosed by its hysteranthous pattern of emergence but is nested among leafless myco-heterotrophic lineages in the lower Epidendroideae. Comprising ca. 80 species distributed across Africa, Asia and Oceania, the genus remains poorly known and plagued by vague and overlapping species circumscriptions, especially within each of a series of taxonomically intractable species complexes. Prior small-scale, exploratory molecular phylogenetic analyses have revealed the existence of cryptic species, but little is otherwise understood of origin, the scale and timing of its biogeographic spread, or the palaeoclimatic factors that have shaped its ecology and given rise to contemporary patterns of occurrence.Methods: Here, we sample widely throughout the generic range, including 45 named taxa and multiple accessions referable to several widespread 'macrospecies', as well as material of equivocal identity and probable undescribed status, for the first time enabling an evaluation of taxonomic boundaries at both species and sectional level. Using nuclear (ITS) and plastid (matK, trnL-F) sequence data, we conduct phylogenetic (maximum parsimony and Bayesian inference) and ancestral area analysis to infer relationships and resolve probable origin and colonisation routes.The genus is strongly supported as monophyletic, as are each of its three sections. However, the number of flowers in the inflorescence and other floral characters are poor indicators of sectional affinity. Dated ancestral area analysis supports an origin in Africa in the Early Oligocene, with spread eastwards to Asia occurring in the Late Miocene, plausibly via the Gomphotherium land bridge at a time when it supported woodland and savanna ecosystems.Discussion: Taxonomic radiation in Asia within the last 8 million years ties in with dramatic Himalayan-Tibetan Plateau uplift and associated intensification of the Asia monsoon. Multiple long-range migrations appear to have occurred thereafter, as the genus colonised Malesia and Oceania from the Pliocene onwards.The bulk of contemporary species diversity is relatively recent, potentially explaining the ubiquity of cryptic speciation, which leaves numerous species overlooked and unnamed. Widespread disjunct species pairs hint at high mobility across continents, extinction and a history of climate-induced vicariance. Persistent taxonomic challenges are highlighted.